The Unseen Malignancy: A case of Abdominal Mesenteric Burkitt’s Lymphoma revealed through imaging: a case report - Jain, Alisha; Ghuliani, (Brig.) Ranjit; Kumar, Pradeep; Swarup, Praneta; Saini, Jitendra; Batra, Sonakshi; Kumar, Cheerla Jayanth (Journal of Neonatal Surgery, 2025)
Burkitt’s lymphoma (BL) is a high-grade, aggressive form of lymphoma that accounts for 8-10% of all paediatric tumors, with abdominal involvement being particularly common. While BL may involve various abdominal regions, the ileum and caecum are the most frequently affected, with primary mesenteric involvement being rare in children. Recent studies have elucidated genetic and molecular underpinnings of different lymphoma subtypes, including the role of chromosomal translocations and genetic aberrations, which provide insights into the pathogenesis of these malignancies and their treatment approaches.